Orthophosphoric Acid Activated Babul Seed Carbon as an Adsorbent for the Removal of Methylene Blue - M. Sujatha; A. Geetha; P. Sivakumar; P. N. Palanisamy (E-Journal of Chemistry)
An Experimental and theoretical study has been conducted on the adsorption of methylene blue dye using activated carbon prepared from babul seed by chemical activation with orthophosphoric acid. BET surface area of the activated carbon was determined as 1060 m2/g. Adsorption kinetics, equilibrium and thermodynamics were investigated as a function of initial dye concentration, temperature and pH. First order Lagergren, pseudo-second order and Elovich kinetic models were used to test the adsorption kinetics. Results were analyzed by the Langmuir, Freundlich and Temkin isotherm models. Based on regression coefficient, the equilibrium data found fitted well to the Langmuir equilibrium model than other models. The characteristics of the prepared activated carbon were found comparable to the commercial activated carbon. It is found that the babul seed activated carbon is very effective for the removal of colouring matter.